1991
DOI: 10.1161/01.hyp.17.6.958
|View full text |Cite
|
Sign up to set email alerts
|

Salt loads raise plasma fatty acids and lower insulin.

Abstract: Some fatty acids are potent inhibitors of angiotensin binding and aldosterone production in adrenal glomerulosa cells and thereby may be involved in regulating salt and water balance. To study the possible regulation of fatty acids by salt, we measured the levels of unesterified fatty acids in plasma from patients subjected to extremes of dietary salt intake and saline infusion. Insulin and catecholamines, two known regulators of plasma fatty acids, also were measured. Infusion of 2 1 saline over 4 hours cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Adipocyte hypertrophy may potentiate the insulin resistance in OP rats, due to the increased fatty acids efflux and increased circulating triglycerides. It was shown that salt increases circulating levels of fatty acids (17), and our data indicating adipocyte hypertrophy suggest a possible increase in circulating fatty acids.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Adipocyte hypertrophy may potentiate the insulin resistance in OP rats, due to the increased fatty acids efflux and increased circulating triglycerides. It was shown that salt increases circulating levels of fatty acids (17), and our data indicating adipocyte hypertrophy suggest a possible increase in circulating fatty acids.…”
Section: Discussionsupporting
confidence: 60%
“…Some forms of hypertension in humans, including essential hypertension associated with obesity, are influenced by an increase in the amount of dietary salt intake (17,53). The aim of the present study was to assess the effect of increased salt intake on the development of hypertension and associated mechanisms involving oxidative stress and endorgan damage in obese rats.…”
Section: Discussionmentioning
confidence: 95%
“…Diacylglycerol-stimulated PKC isoforms serine-phosphorylate IRS-1 and IRS-2, inactivating the downstream PI3-kinase needed for translocation of GLUT 4 to the cell membrane 34 . A high salt intake may enhance this mechanism because it results in a 33% increase in plasma free fatty acids 35 . Indirect effects of obesity may include activation of sympathetic nervous system activity 33 or inadequate suppression of aldosterone by salt 36 .…”
Section: Discussionmentioning
confidence: 99%
“…differences in feed intake or body weight. A strong direct effect of salt (dietary intake or infused) on insulin concentration has been reported in non-pregnant humans (Goodfriend et al, 1991) but the mechanism is not known. An earlier study with wethers found that plasma concentrations of insulin concentration decreased in wethers fed 20% NaCl for 14 days (Blache et al, 2007) and our results extend the work by Blache et al (2007) by showing a persistent (i.e.…”
Section: Discussionmentioning
confidence: 99%